Retrofit of an Historical Building toward NZEB. (November 2015) - Mora, T. Dalla; Cappelletti, F.; Peron, F.; Romagnoni, P.; Bauman, F.
Abstract: The European Directive on Energy Efficiency in Buildings (Directive 2010/31/EU) has introduced the need to transform buildings to nearly zero energy (NZEB) by 2020. Existing buildings represent the major part of the building stock and an interesting challenge is to transfer it toward NZEB. Energy retrofit is even more significant in Italy, where existing buildings stock (mainly residential) is also historic, so it's subject to environmental constraints or architectural-artistic value, and it's influenced by specific regulations and methods of intervention for refurbishment. In this case, the challenge becomes even more important and concerns both the building shell and the systems: retrofitting introduces not originally present in the complex; retrofit is not covered in the maintenance, since it represents an upgrade, an adaptation of the building, specifically in relation to energy efficiency, but also, by extension, other functions / features pertaining to the environment and sustainability. A case study of a radical refurbishment of an historical building is Ca' S. Orsola in Treviso. It is ruled by the Historical and Architectural Veneto Regional Authority. The building has been transformed into a prestigious residential complex by a major renovation that was aimed primarily seismic and energy upgrading. The energy and environmental performance of building have been analyzed by numerical simulation and experimental measurement in the EBC IEA Annex 56[1] context with the aim to verify that intervention strategies respect to the reduction of energy consumption, the minimization of CO2 emissions and maximizing the use of sources of renewable energy.